Determination of Trace Elements and Heavy Metals in Selenium-Enriched Malt Powder by ICP-MS - Zhang, Hongxing; Rui, Yukui (Asian Journal of Chemistry, 2013)
Selenium is an essential element for human health, plays an irreplaceable role on human aging and disease prevention. Selenium-enriched malt powder is an important health care products enriched selenium, selenium - enriched malt powder should be safe as food. Today the role of other trace elements and safety of heavy metals in selenium - enriched malt powder are ignored. In this study, selenium-enriched malt powder produced by Beijing Sevkon ecological science and technology Co., Ltd was determined the trace elements and heavy metals. The results showed that the content of selenium produced by Beijing Sevkon ecological science and technology Co. Ltd. is higher than normal malt and other brands of selenium-enriched malt powder; the content of some heavy metals in enriched malt powder exceed the national standards. We should pay particular attention to their food safety. A national standard of selenium-enriched food production should be developed as soon as possible to promote the standardization and scientific production of the selenium-enriched product.